1997
DOI: 10.1590/s0100-879x1997001200011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture on behavioral, cardiovascular and hormonal responses in restraint-stressed Wistar rats

Abstract: Stress is a well-known entity and may be defined as a threat to the homeostasis of a being. In the present study, we evaluated the effects of acupuncture on the physiological responses induced by restraint stress. Acupuncture is an ancient therapeutic technique which is used in the treatment and prevention of diseases. Its proposed mechanisms of action are based on the principle of homeostasis. Adult male Wistar EPM-1 rats were divided into four groups: group I (N = 12), unrestrained rats with cannulas previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 9 publications
0
9
0
2
Order By: Relevance
“…These findings are consistent with previous studies showing that acupuncture can reduce expression of c-Fos and CREB, as a non-specific marker, in several stress-related structures after exposure to stress (Kim et al 2009; Liu et al 2005). Several studies have demonstrated that acupuncture plays an anxiolytic role in stress-induced neurochemical and behavioral responses (Guimaraes et al 1997; Lee et al 2004). Moreover, acupuncture attenuates stress-induced physiological responses via a central GABA pathway (Iwa et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with previous studies showing that acupuncture can reduce expression of c-Fos and CREB, as a non-specific marker, in several stress-related structures after exposure to stress (Kim et al 2009; Liu et al 2005). Several studies have demonstrated that acupuncture plays an anxiolytic role in stress-induced neurochemical and behavioral responses (Guimaraes et al 1997; Lee et al 2004). Moreover, acupuncture attenuates stress-induced physiological responses via a central GABA pathway (Iwa et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, examples of such an influence, the somatovisceral reflex, have already been demonstrated (35) and comprise one of the proposed mechanisms of action of acupuncture (36)(37)(38). Therefore, it is reasonable to speculate that visceral function, particularly of the stomach in our experiment, is influenced by stimulation of the corresponding somatic area, thus preventing gastric ulcers induced by indomethacin.…”
Section: Discussionmentioning
confidence: 58%
“…epinephrine, norepinephrine, corticosterone, etc.) (30–32). For example, acupuncture stimulation of ST‐36 may increase adrenocortical hormone production in awake rabbits and may, in turn, inhibit adrenocortical hormone production which is induced by immobilization, heat, or cold exposure (30,31).…”
Section: Discussionmentioning
confidence: 99%